Canadian Association of Radiologists Recommendations for the Safe Use of MRI During Pregnancy. Issue 1 (February 2022) - Jabehdar Maralani, Pejman; Kapadia, Anish; Liu, Grace; Moretti, Felipe; Ghandehari, Hournaz; Clarke, Sharon E.; Wiebe, Sheldon; Garel, Juliette; Ertl-Wagner, Birgit; Hurrell, Casey; Schieda, Nicola
The use of magnetic resonance imaging (MRI) during pregnancy is associated with concerns among patients and health professionals with regards to fetal safety. In this work, the Canadian Association of Radiologists (CAR) Working Group on MRI in Pregnancy presents recommendations for the use of MRI in pregnancy, derived from literature review as well as expert panel opinions and discussions. The working group, which consists of academic subspecialty radiologists and obstetrician-gynaecologists, aimed to provide updated, evidence-based recommendations addressing safety domains related to energy deposition, acoustic noise, and gadolinium-based contrast agent use based on magnetic field strength (1.5T and 3T) and trimester scanned, in addition to the effects of sedative use and occupational exposure.